Upper and Lower Continuity of Fuzzy Soft Multifunctions - Metin Akdağ; Serkan Karataş; Fethullah Erol (Journal of New Theory)
− In this paper, we define the upper and lower inverse of a fuzzy soft multifunction andprove some basic identities. Then by using these ideas we introduced the concept of fuzzy soft continuity and obtain many interesting properties of upper and lower fuzzy soft continuous multifunctions